Variations in the human mandibular canal and foramina: A CBCT study / Saif Yousif Abdullah - Saif Yousif , Abdullah (2017)
The increased neurological clinical complications after surgical intervention in the mandible necessitate the demand for precise detection of the mandibular canal and its foramina variations prior to any surgical intervention. Aims: To identify and classify variations of the mandibular canal and foramina in dentate Malaysian using Cone-Beam Computed Tomography (CBCT). Materials and Methods: The subjects for this study were 202 who had attended the Oral Radiology Division, Faculty of Dentistry, University of Malaya for CBCT screening. Using the dataset generated, bifid/trifid mandibular canals were identified and classified. Their vertical location, diameter, lumen shape were studied. The location of the mental foramen, mental foramen opening distance, orientation of the opening, the location of the mandibular foramen, the prevalence of accessory mental and mandibluar foramina and retromolar foramen were studied in detail. To enhance the quality of images studied, SimPlant software was employed and the findings analysed using statistical software (SPSS v.12). Results: In the present study, bifid mandibular canal were observed in 46 (22.77%) patients with the retromolar canal being the most numerous. The mean length of the bifid mandibular canals was 32.33mm ±19.96 (range: 7.20-86.33mm). The mean diameter of the bifid mandibular canal was 1.42 mm (SD ±0.32). Fifty-six percent of bifid mandibular canals were below the main mandibular canal. Trifid mandibular canals were observed in 12 (5.9%) of the 202 patients and retromolar canal was again the most frequent type recorded. The mean diameter of the trifid mandibular canal was 1.29 mm (SD ± 0.23) (range: 0.93-1.89 mm) and the mean length was 20.75 mm ± 14.43 (range: 5-52mm). Forward canal type has the longest trifid mandibular canal length while the retromolar canal was the shortest. With regards to the mental foramina, they were located 10.9 mm from the lingual cortex and 14 mm above the lower edge of the mandible while the mandibular foramen was 5.89 mm from the buccal edge of the mandibular foramen perpendicularly to the buccal cortical margin of the ramus and 23.26 mm above the lower edge of the mandible. Accessory mental foramina were observed in 5 (1.2%), accessory mandibular foramina were observed in 19 (4.9%) and retromolar foramina were observed in 28 (7.2%) of the 388 hemi-mandibles studied. Conclusion: This study revealed that there is a high prevelance of variations in the number of mandibular canal among Malaysians and that the ―retromolar canal‖ type is the most common type of the mandibular canal variation in this population. The ability to visualise and quantify precisely these complicated variations using CBCT provides support for the view that this imaging modality should become the recognised standard of care before any mandibular surgery.